Field-Trip–Based Outdoor Learning Improves Pantun Writing: A Quasi-Experimental Study in an Indonesian Junior High School - Cintia Cintia; Ahmad Suradi; Dina Putri Juni Astuti (JPI: Jurnal Pustaka Indonesia, 2024)
This study examined whether a brief, curriculum-aligned field trip (karyawisata) improves Grade-level students’ ability to write pantun (Indonesian rhymed quatrains). Using a quasi-experimental nonequivalent control-group design in one Indonesian school, two intact classes were assigned to an outdoor-learning sequence (n = 8) or business-as-usual classroom instruction (n = 7). The intervention comprised a genre pre-briefing, directed environmental observation with note sheets, and in-class drafting plus peer/teacher conferencing mapped explicitly to pantun structure (sampiran–isi, imagery, rhyme). Outcomes were assessed with an analytic rubric; two blinded raters scored all scripts and achieved good inter-rater reliability (ICC), and assumption checks supported parametric inference (normality and homogeneity satisfied). Results showed that the experimental class outperformed the control class on the post-test (M = 83.75 vs 71.43), with an independent-samples t confirming a statistically significant advantage, t(13) = 2.236, p = 0.043, mean difference = 12.32 (95% CI [0.42, 24.22]); the standardized effect was large (Hedges’ g ≈ 1.09). Dimension-level patterns indicated the largest gains precisely where the pedagogy targeted imagery & diction and sampiran–isi coherence with positive, smaller trends for rhyme adherence and rhythm/fluency. We conclude that a short, structured field-trip cycle can measurably enhance pantun writing under routine school conditions when observation prompts and feedback loops are aligned with genre features. Schools can timetable compact outdoor-learning units equipped with behavior-anchored rubrics and safety/management SOPs; teacher education should model task–assessment alignment for genre writing; and future research should scale to multi-site clustered trials, include delayed post-tests for retention, and test transfer to other poetry/essay genres.